E-LEARNING APPLICATION AS A ISLAMIC MENTORING ON LEARNING SYSTEM OF INFORMATICS ENGINEERING STUDENTS - Setiawan, Wahyu; Qurrohman, Taufiq; Kurniawan, Fachrul (Letters in Information Technology Education (LITE), 2019)
Information technology is developing very fast and is increasingly strengthened by the existence of the internet that has spread throughout the world. With the internet, the flow of information is increasingly spinning to the public and information technology applications have begun to emerge. These applications make it easy for people who use them, including e-mail, video conferences, mailing lists, chat, e-learning, and others. This paper implements an e-learning system as an Islamic mentoring in the Department of Information Engineering. The e-learning system has the potential to make the mentoring process more effective, because the interaction are wider open. Mentees can communicate with their mentors anytime via the internet. Through e-learning, mentees can continue learning even if they are not physically present at weekly mentoring meetings. Mentoring activities become very flexible because it can be adjusted to the availability of mentee time. Learning activities occur through mentee interaction with learning resources available in e-learning applications and can be accessed from the internet. This e-learning application can be used as a supporting facility of Islamic religious mentoring using conventional methods where mentoring participants meet weekly with their respective mentors. With e-learning applications on Islamic mentoring, mentees can interact with their mentors wherever and whenever they are. With the prerequisites, they are connected to the internet.